Comparison of digital PCR and real time PCR methods for quantitative analysis of African Swine Fever Virus - Dei Giudici, Silvia; Bonelli, Piero; Tilocca, Maria Giovanna; Cau, Simona; Angioi, Pier Paolo; Sechi, Anna Maria; Vodret, Bruna; Oggiano, Annalisa (Frontiers in Veterinary Science, 2025)
IntroductionThe African swine fever (ASF) is a viral disease of significant socio-economic and animal health impact, commonly diagnosed using molecular techniques. The World Organization of Animal Health (WOAH) has recommended two highly sensitive and specific real time polymerase chain reaction (PCR) procedures (P1 qPCR and P2 qPCR) for the reliable and rapid detection of the ASF virus (ASFV). The present work aimed to standardize two third-generation PCR technologies by using the same WOAH-recommended primer/probe sets.MethodsWe developed two droplet digital PCR protocols ddPCRs and compared their analytical performances to the above-mentioned qPCRs. This involved testing serially diluted plasmid containing the vp72 gene sequence of the ASFV as the template. Clinical positive and negative samples were also analyzed to compare both PCR procedures.Results and discussionThe ddPCR assays demonstrated excellent linearity (R2 = 0.999) across a dynamic range from 104 to 1 copies/μl. The limits of detections (LOD) were 3.48 and 2.80 copies/μl and the limit of quantifications (LOQs) were ranging from 25 and 20 copies/μl for the P1 and the P2 procedures, respectively. The LOD values were comparable to those of qPCRs assays. The analysis of the clinical samples evidenced a strong agreement between the qPCR and the ddPCR, with bias values below 0.20, as determined by Bland-Altman analysis. The results of this study indicated that the ddPCR method can be adapted to existing validated qPCR protocols, enabling the quantification of low viral titer samples with similar analytical sensitivity. Moreover, the use of ddPCR allows for the absolute quantification without the need of a calibration curve, providing a reliable tool for ASFV diagnosis and outbreak management. It could also support global effort to control the spread of ASFV. Further validation in diverse matrices (e.g., feed and environmental swabs) could expand its applicability in the One Health frameworks.